Great Olympians
On these pages, you will find lists of individuals who have achieved memorable achievements in the Olympic Games, from 1896 up to and including 1998. For all, a complete listing is given of the medals and diplomas each has won. For many individuals, a biography is included. Here are the lists : 80 people who have won gold in the same event in three Olympiads. 16 people who could have joined this exclusive list at Nagano (4 did). 32 people could join this list at Sydney 25 people who have won gold in a different event in three Olympiads. and some 350 people who have won any sort of medal in the same event in three Olympiads. 11 people who have won gold at four (or more) Olympics. My own TOP-600 of Olympians (including two horses : Absent and Marcroix), according to a special count - Honour Points - I devised for this. (1-200)(200-400)(400-600)(others) The Top Olympians of Nagano by the same count You can check this list by country Or by Sport Here are Olympians who have competed succesfully at more than one sport Here are all individuals who have won 5 or more medals, of whatever colour. Or you can simply browse the biographies, starting with the letter.